Sobre a luz e as potências do escuro na fotografia: imagens técnicas de alcova no cinema - Polidoro, Bruno Bortoluz (Universidade do Vale do Rio do Sinos, 2009)
The present thesis is inserted in the Media and Audiovisual Processes research line, and its general objective is to discuss photography – and light, especially – as an update of the dark in audiovisuals. The theoretical basis is built mainly from concepts proposed by Vilém Flusser, Henri Bergson, Gilles Deleuze, Jacques Aumont and Jean-Paul Sartre. Focusing on cinema, the analysis is made of movies in which there are sex scenes; points out in these technical images the interference of photography in the formulation of filmic concepts; and outlines some games from lights and shadows created by a liquid light. The methodology rizomatically combined the deconstruction, the cartography and the dissection, and made the authentication of framings intrinsic to the lighting and to the alcove photographic images construction possible.
Keywords: audiovisualidades; cinema; conceitos fílmicos de sexo; imagens técnicas; fotografia; audiovisualities; cinema; filmic sex concepts; technical image; photography; Ciências Sociais Aplicadas